Conserving the Yellowstone National Park Ecosystem through Gray Wolves (Canis lupus) ... - Lambert, Aquila (Maryland Shared Open Access Repository, 2022)
Gray wolves are a keystone species in the Yellowstone National Park (YNP) ecosystem because they can restore balance to and regulate a previously unhealthy ecosystem. The true value of gray wolves as a keystone species was not realized until decades after their reintroduction in 1995. Over time, gray wolves’ predatory habits decreased elk populations, which allowed for vegetation to grow back and other herbivores to repopulate. Despite gray wolves’ overwhelmingly positive effect on the YNP ecosystem, they are hunted illegally for sport or by farmers to protect livestock. Currently, disease and human hunting are the biggest threats to the long-term success of gray wolves in YNP. ...